1998
DOI: 10.1111/j.1399-6576.1998.tb05082.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anaesthesia based on high versus low doses of opioids on the cytokine and acute‐phase protein responses in patients undergoing cardiac surgery

Abstract: CABG performed during two different anaesthetic techniques, high-dose fentanyl versus low-dose opioid anaesthesia, elicited a well-defined cytokine response with minor variation in the time course of each cytokine. The cytokine production was not modified by type of anaesthesia. Finally, SAP is not an acute-phase protein in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 24 publications
1
45
2
6
Order By: Relevance
“…This response seems to be paralleled by IL-8 as a reaction to major surgery [26]. No detectable TNF-α response in plasma has so far been demonstrated following surgery apart from cardiac surgery [27].…”
Section: Discussionmentioning
confidence: 99%
“…This response seems to be paralleled by IL-8 as a reaction to major surgery [26]. No detectable TNF-α response in plasma has so far been demonstrated following surgery apart from cardiac surgery [27].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with established SIRS or organ dysfunction both pro-and anti-inflammatory cytokines are detectable in markedly increased amounts in peripheral blood. We have previously demonstrated that the CPB procedure itself induces a well-defined pro-and anti-inflammatory cytokine response in neonatal pigs (5) analogous to the human response to cardiac surgery performed during CPB (6,7). However, plasma levels of cytokines do not necessarily reflect tissue concentrations or their effect at organ level and may therefore be a poor reflection of the processes occurring at organ level.…”
mentioning
confidence: 99%
“…Im Plasma herzchirurgischer Patienten, bei denen zwischen einem Anästhesieregime mit hoch bzw. niedrig dosiertem Fentanyl unterschieden wurde, war die Konzentration von IL-8, IL-6 und IL-10 bei beiden Narkoseverfahren vergleichbar [12].…”
Section: Fehlende Direkte Immunmodulation Durch Fentanylunclassified